Pathogenicity of In Vivo Generated Intestinal Th17 Lymphocytes is IFNγ Dependent. (25th April 2018) - Nizzoli, Giulia; Burrello, Claudia; Cribiù, Fulvia Milena; Lovati, Giulia; Ercoli, Giulia; Botti, Fiorenzo; Trombetta, Elena; Porretti, Laura; Todoerti, Katia; Neri, Antonino; Giuffrè, Maria Rita; Geginat, Jens; et al.
Abstract: Background and Aims: T helper 17 [Th17] cells are crucially involved in the immunopathogenesis of inflammatory bowel diseases in humans. Nevertheless, pharmacological blockade of interleukin 17A [IL17A], the Th17 signature cytokine, yielded negative results in patients with Crohn's disease [CD], and attempts to elucidate the determinants of Th17 cells' pathogenicity in the gut have so far proved unsuccessful. Here, we aimed to identify and functionally validate the pathogenic determinants of intestinal IL-17–producing T cells. Methods: In vivo– generated murine intestinal IL-17–producing T cells were adoptively transferred into immunodeficient Rag1 –/– recipients to test their pathogenicity. Human IL-17, IFNγ/IL-17, and IFNγ actively secreting T cell clones were generated from lamina propria lymphocytes of CD patients. The pathogenic activity of intestinal IL-17–producing T cells against the intestinal epithelium was evaluated. Results: IL-17–producing cells with variable colitogenic activity can be generated in vivo using different experimental colitis models. The pathogenicity of IL-17–secreting cells was directly dependent on their IFNγ secretion capacity, as demonstrated by the reduced colitogenic activity of IL-17–secreting cells isolated from IFNγ –/– mice. Moreover, IFNγ production is a distinguished attribute of CD-derived lamina propria Th17 cells. IFNγ secretion by CD-derived IL-17–producing intestinal clones is directly implicated in the epithelial barrier disruption through the modulation of tight junction proteins. Conclusions: Intestinal Th17 cell pathogenicity is associated with IFNγ production, which directly affects intestinal permeability through the disruption of epithelial tight junctions.